Determinanten der Outplacement-Gewährung: Ergebnisse einer theoriegeleiteten empirischen Analyse - Dorothea Alewell; Kerstin Pull (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2009)
In times of massive employment reduction, outplacement services are increasingly popular. However, the empirical knowledge of the provision of outplacement services is limited. In our paper we present the results of an original survey of more than 1,000 German firms that systematically renders information on the use of externally provided outplacement services in Germany as well as on the determinants of outplacement provision. Theoretically we recur on the work by Pull (2008) who unfolds different rationales of outplacement provision, and derive implications for the determinants of outplacement provision. In a second step the implications from theory are confronted with empirical evidence. Our empirical analysis renders support for an accounting-based logic of outplacement provision according to which the provision of outplacement services is motivated by immediate and direct cost savings, as well as for a signalling based logic where firms use the provision of outplacement services as a signal to future job applicants. Implications based on gift exchange theory as well as those based on collective bargaining do not find support in the data.
Keywords: 330; Personalabbau; berufliche Reintegration - Förderung; Unternehmen